Teachers’ Experiences in Online Teaching and Learning Modality - Capacio, Leadean Jay A.; Celesio, Gilbert A.; Naparan, Genesis B. (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
This study explores Teachers' Experiences in Online Teaching and Learning Modality. The participants were selected private school elementary teachers in Pagadian City offering Online Modality in School Year 2020-2021. The study was based on the interpretivist paradigm since the researcher used social skills to construct knowledge and meaning. Case study was utilized. Teachers' experiences include perception, way of delivering instruction using online platforms, struggles, adjustments, and suggestions for improvement. The study is supported with data from multiple sources: Interview Guide Questions, Principals’ Evaluation Form, and Researcher’s Checklist. Participants perceived online modality as agent of continuity of learning, and challenging. It showed that Zoom teleconferencing is the preferable online platform to use. The participants’ struggles were power interruption, poor internet connectivity, computer technology operations, imposition of classroom management, lack of preparation, and getting used to another personal work-schedule. The participants' adjustments pointed to acceptance of situation, self-exploration, asking teaching materials, and knowledge-skill support from the school. The participants and principals' responses led to attending trainings regarding Online Teaching Methodology in general. Based on the findings, the researcher recommends to the outmost possibility that there may be ICT trainings, provision of upgraded internet connectivity and gadgets, reducing workload and class size.